2015
DOI: 10.24297/jssr.v8i1.3602
|View full text |Cite
|
Sign up to set email alerts
|

Can Governance in Revenue Sharing Be a Pathway for a Win-win Situation between Peoples Livelihood Improvement and Conservation

Abstract: This paper establishes the importance of good governance in improving local livelihoods and support for conservation. The study uses empirical realities from Bwindi Impenetrable National Park, an afromontane Gorilla sanctuary that was recognized by UNESCO in 2005 as a world heritage due to its rich biodiversity. Governance is an important procedural dimension of equity that entails decision making processes and how local people are involved in matters that most affect them. The paper uses a Policy Arrangements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
(12 reference statements)
1
5
0
Order By: Relevance
“…There is a growing need for greater involvement of local people in decision making. This is in agreement with Martin et al (2016) and Twinamatsiko et al (2015) that found there is a positive relationship between local involvement and conservation support. Dawson et al (2017) further articulates the conservation outcome generated as a result of respecting and valuing other conservation stakeholders.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…There is a growing need for greater involvement of local people in decision making. This is in agreement with Martin et al (2016) and Twinamatsiko et al (2015) that found there is a positive relationship between local involvement and conservation support. Dawson et al (2017) further articulates the conservation outcome generated as a result of respecting and valuing other conservation stakeholders.…”
Section: Discussionsupporting
confidence: 91%
“…Greater governance and equity strengthen community support for conservation and development. This revelation relates to the finding by Twinamatsiko et al (2015) that the more people felt involved and that they benefited from Bwindi Impenetrable National Park, the more they increased their conservation support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participatory decision-making was officially adopted as a conventional conservation approach in 1982, following the 3rd World Park Congress, which acknowledged the value of community participation in forest management for the sustainable use of natural resources (Twinamatsiko et al, 2015;Nabanyumya et al, 2017). The involvement of local communities was re-echoed at the United Nations Conference on Environment and Development (UNCED), held in Rio de Janeiro in June 1992.…”
Section: Introductionmentioning
confidence: 99%